Cultures and societies in a changing world - Griswold, Wendy; SAGE Knowledge (Online service). (Thousand Oaks, Calif. Sage, 2013)
"In the Fourth Edition of Cultures and Societies in a Changing World, author Wendy Griswold illuminates how culture shapes our social world and how society shapes culture. Through this book, students will gain an understanding of the sociology of culture and explore stories, beliefs, media, ideas, art, religious practices, fashions, and rituals from a sociological perspective. Cultural examples from multiple countries and time periods will broaden students' global understanding. Students will develop a deeper appreciation of culture and society from this text, gleaning insights that will help them overcome cultural misunderstandings, conflicts, and ignorance and that will help equip them to live their professional and personal lives as effective, wise citizens of the world."-Provided by publisher.
About the author -- Foreword -- Preface -- Culture and the cultural diamond -- Cultural meaning -- Culture as a social creation -- The production, distribution, and reception of culture -- Identities, problems, and movements -- Organizations in a multicultural world -- Culture and connection -- Culture and power.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Culture; Social change; Electronic books